2015
DOI: 10.1037/tra0000038
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for trauma treatment: A systematic review of the empirical literature.

Abstract: The prevalence of trauma histories and related psychological problems is high in general clinical settings, but little is known about trauma patient preferences for mental health treatment. The purpose of this article is to systematically review and synthesize the literature on treatment preferences in survivors of traumatic events. Studies were identified using comprehensive searches of PsycINFO, Medline, PubMed, Published International Literature on Traumatic Stress, and Cumulative Index to Nursing and Allie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
5
31
2
Order By: Relevance
“…Although most existing research on trauma treatment preferences (as well as research on mood/anxiety treatment in general; McHugh et al, 2013) indicates a preference for psychotherapy over medication (Simiola et al, 2015), our findings diverged in that the largest proportion of veterans engaged in both psychotherapy and pharmacotherapy, which was followed by veterans who engaged in pharmacotherapy only. There are important differences between our study and most of those reviewed in the Simiola et al (2015) article; namely, all participants in the current study were treatment-seeking, diagnosed with PTSD, and had a choice about what treatment to engage in (including the option for both psychotherapy and pharmacotherapy) rather than being asked about hypothetical preference in an either/or scenario. It is possible that individuals who do not actually have PTSD or were not actually exposed to trauma may theoretically prefer psychotherapy to pharmacotherapy (the Semiola article included analogue samples), but those who are currently suffering from PTSD want to consider medication.…”
Section: Discussioncontrasting
confidence: 84%
“…Although most existing research on trauma treatment preferences (as well as research on mood/anxiety treatment in general; McHugh et al, 2013) indicates a preference for psychotherapy over medication (Simiola et al, 2015), our findings diverged in that the largest proportion of veterans engaged in both psychotherapy and pharmacotherapy, which was followed by veterans who engaged in pharmacotherapy only. There are important differences between our study and most of those reviewed in the Simiola et al (2015) article; namely, all participants in the current study were treatment-seeking, diagnosed with PTSD, and had a choice about what treatment to engage in (including the option for both psychotherapy and pharmacotherapy) rather than being asked about hypothetical preference in an either/or scenario. It is possible that individuals who do not actually have PTSD or were not actually exposed to trauma may theoretically prefer psychotherapy to pharmacotherapy (the Semiola article included analogue samples), but those who are currently suffering from PTSD want to consider medication.…”
Section: Discussioncontrasting
confidence: 84%
“…Comparing narrative exposure therapy with present-centred therapy for older patients treatment method; 48,49 providing balanced information fosters realistic expectations and hence better results.…”
Section: Discussionmentioning
confidence: 99%
“…NET, however, should be the treatment of choice if patients prefer sharing their trauma story and adapting its meaning in their lives. Patient and therapist preferences have been shown to play an important role in the choice of treatment method; 48,49 providing balanced information fosters realistic expectations and hence better results.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that these patient-related treatment issues are largely based on the opinions of therapists [ 10 , 11 , 12 ]. Where studies have focused on patient treatment preferences, patients tend to opt for trauma-focused strategies over other psychotherapies, and the opportunity to talk about their trauma [ 13 , 14 ]. In contrast, therapist-focused research has reported therapists’ own reluctance to implement trauma-focused treatments with concerns including fear of “opening Pandora’s box”, limited belief in the credibility of treatments, or doubting their own competence [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%